Vascular endothelial growth factor and endocan expression in adrenal cortical tumors and their relationship with histopathological prognostic parameters - Karaköse, Melia; Kocabaş, Muhammet; Can, Mustafa; Karakurt, Feridun; Kulaksızoğlu, Mustafa; Esen, Hacı Hasan (Endocrine Journal, 2024)
The aim of this study was to determine the tissue expressions of vascular endothelial growth factor (VEGF) and endocan in adrenal cortical tumors and the factors associated with them. The study included 6 subjects with adrenocortical adenoma (ACA), 7 subjects with adrenocortical carcinoma (ACC), and 13 control subjects with a normal adrenal cortex. The status of VEGF and endocan expression was determined by the proportions of cells staining on a scale ranging from negative (not staining at all) to strongly positive. VEGF expression was detected in 1 (16.7%) of 6 subjects in the ACA group and in 6 (85.7%) of 7 subjects in the ACC group. VEGF expression was not detected in any of the subjects in the control group. Endocan expression was detected in 6 (100%) of 6 subjects in the ACA group and in 7 (100%) of 7 subjects in the ACC group, while it was detected in only 4 (30.7%) of 13 subjects in the control group. VEGF was expressed with a high frequency in subjects with ACC and with a low frequency in subjects with ACA, but it was not expressed in subjects with normal adrenal cortex tissue. Although endocan was expressed with a higher frequency in subjects with ACC and ACA, it was also expressed in subjects with normal adrenal cortex tissue. The percentage of cells expressed endocan in subjects with ACC was also significantly higher than in subjects with both ACA and normal adrenal cortex.